Postprandial dynamics and response of fibroblast growth factor 21 in older adults. Issue 6 (June 2021) - Herpich, Catrin; Haß, Ulrike; Kochlik, Bastian; Franz, Kristina; Laeger, Thomas; Klaus, Susanne; Bosy-Westphal, Anja; Norman, Kristina
Summary: Background & aims: Fibroblast growth factor 21 (FGF21) plays a pivotal role in glucose and lipid metabolism and has been proposed as a longevity hormone. However, elevated plasma FGF21 concentrations are paradoxically associated with mortality in higher age and little is known about the postprandial regulation of FGF21 in older adults. In this parallel group study, we investigated postprandial FGF21 dynamics and response in older (65–85 years) compared to younger (18–35 years) adults following test meals with varying macronutrient composition. Methods: Participants (n = 60 older; n = 60 younger) were randomized to one of four test meals: dextrose, high carbohydrate (HC), high fat (HF) or high protein (HP). Blood was drawn before and 15, 30, 60, 120, 240 min after meal ingestion. Postprandial dynamics were evaluated using repeated measures ANCOVA. FGF21 response was assessed by incremental area under the curve. Results: Fasting FGF21 concentrations were significantly higher in older adults. FGF21 dynamics were affected by test meal (p < 0.001) and age (p = 0.013), when adjusted for BMI and fasting FGF21. Postprandial FGF21 concentrations steadily declined over 240 min in both age groups after HF and HP, but not after dextrose or HC ingestion. At 240 min, FGF21 concentrations were significantly higher in older than in younger adults following dextrose (133 pg/mL, 95%CI: 103, 172 versus 91.2 pg/mL, 95%CI: 70.4, 118; p = 0.044), HC (109 pg/mL, 95%CI: 85.1, 141 versus 70.3 pg/mL, 95%CI: 55.2, 89.6; p = 0.014) and HP ingestion (45.4 pg/mL, 95%CI: 34.4, 59.9 versus 27.9 pg/mL 95%CI: 20.9, 37.1; p = 0.018). FGF21 dynamics and response to HF were similar for both age groups. Conclusions: The age-specific differences in postprandial FGF21 dynamics and response in healthy adults, potentially explain higher FGF21 concentrations in older age. Furthermore, there appears to be a significant impact of acute and recent protein intake on FGF21 secretion.